Pengembangan Aplikasi Pencarian Rumah Kos Dengan Metode Scrum Dalam Rangka Digitalisasi UMKM Di Desa Popalia - Suharsono Bantun; Jayanti Yusmah Sari (Faculty of Computer Science, University of Jember, 2023)
The Covid-19 pandemic has also had an impact on UMKM. Boarding house businesses are included in UMKM which are located in school or campus areas. As a result of the pandemic, many boarding house businesses around campus have been abandoned because of the WFH and SFH policies. After 2 years, now schools and campuses have started to be active again. These conditions can revive the boarding house business around the USN Kolaka campus in Popalia Village. Based on the results of observations and interviews with students and boarding house owners, problems were found in efforts to revive the post- pandemic boarding house business, including: 1) students as the target consumer had difficulty obtaining boarding house information; 2) there is no info on the location map of the boarding house; 3) boarding house owners still use manual methods to promote their boarding houses. From these problems, it is necessary to digitize boarding houses, one of which is by making applications that can provide clear and up-to-date information. This study aims to develop a boarding house search application using the scrum method. The results of this study succeeded in making the popakos.com application according to user needs with a processing time of 54 days.